PENGARUH KONFLIK PERAN TERHADAP TERJADINYA BURNOUT PADA MAHASISWA KOASS - Anggita Amelia Pangesti (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2012)
Abstract The study was conducted 49 co-ass students who are doing clinical practice (N=49), investigate the effect of role conflict with the occurrence of burnout. Using a purposive technique sampling, these studies make use of two instruments as a measure of role conflict and burnout measurement tools that has been modified from the Maslach Burnout Inventory (MBI) with Likert models. The result is that there is significant influence between role conflict and the occurrence of burnout in co-ass students. The amount of influence (R Square) to the occurrence of role conflict and burnout is 0.389 (38.9%) which means that the conflict affects the role of burnout by 38.9% and the remaining 61.1% influenced by other factors outside of role conflict. This indecated any significant positive effect of role conflict and the occurrence of burnout. Keywords: co-ass, role conflict, burnout